Closure to Discharge Characteristics of a Trapezoidal Labyrinth Side Weir with One and Two Cycles in Subcritical Flow by M. Emin Emiroglu, M. Cihan Aydin, and Nihat Kaya - Emiroglu, M. Emin; Aydin, M. Cihan; Kaya, Nihat (Asce-Amer Soc Civil Engineers, 2015)
[Abstract Not Available]